2022
DOI: 10.1001/jamanetworkopen.2021.45876
|View full text |Cite
|
Sign up to set email alerts
|

Association of Spinal Cord Stimulator Implantation With Persistent Opioid Use in Patients With Postlaminectomy Syndrome

Abstract: IMPORTANCEThe results of studies evaluating spinal cord stimulation (SCS) for postlaminectomy syndrome (PLS) have yielded mixed results. This has led to an increased emphasis on objective outcome measures such as opioid prescribing.OBJECTIVE To determine the association between SCS and long-term opioid therapy (LOT) for PLS. DESIGN, SETTING, AND PARTICIPANTSIn this cohort study, adults with PLS were identified using the TriNetx Diamond Network and separated based on whether they underwent SCS. Patients were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…A prior meta-analysis of 5 clinical trials, 4 of which were industry funded, found a minor reduction in opioid use after SCSs compared with CMM . In contrast, a recent independent study with 1-year follow-up of patients postlaminectomy found small, clinically questionable opioid discontinuation associated with SCSs . We extend these findings to 2 years and several additional endpoints among a broader population receiving SCS for multiple indications.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A prior meta-analysis of 5 clinical trials, 4 of which were industry funded, found a minor reduction in opioid use after SCSs compared with CMM . In contrast, a recent independent study with 1-year follow-up of patients postlaminectomy found small, clinically questionable opioid discontinuation associated with SCSs . We extend these findings to 2 years and several additional endpoints among a broader population receiving SCS for multiple indications.…”
Section: Discussionmentioning
confidence: 53%
“…27 In contrast, a recent independent study with 1-year follow-up of patients postlaminectomy found small, clinically questionable opioid discontinuation associated with SCSs. 28 We extend these findings to 2 years and several additional endpoints among a broader population receiving SCS for multiple indications. SCSs may also be associated with harm in some patients.…”
Section: Discussionmentioning
confidence: 60%
“…The widespread and increasing use of spinal cord stimulation for persistent pain following lumbar spine surgery does not appear to result in clinically meaningful cessation of opioids or improvement in pain or disability. [42][43][44]…”
Section: Discussionmentioning
confidence: 99%
“…Although these results were among a different subpopulation of surgical patients, we strongly encourage clinical trials where patients with, or at risk of opioid abuse are provided interventions aiming at cessation or tapering opioid use. The widespread and increasing use of spinal cord stimulation for persistent pain following lumbar spine surgery does not appear to result in clinically meaningful cessation of opioids or improvement in pain or disability 42–44 …”
Section: Discussionmentioning
confidence: 99%
“…However, the literature is conflicting regarding whether these devices reduce opioid use 30,[50][51][52][53] , especially to a clinically significant degree 30 . Hwang et al found that 20% of patients had a decreased daily opioid dose a year after SCS implantation compared with preoperative doses while 40% saw no change.…”
Section: Scssmentioning
confidence: 99%